DETEKSI DINI PERILAKU PENYIMPANGAN SEKSUAL MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Nur Rochmah Dyah Puji Astuti; Yoga Putra Pamungkas (JURNAL INFORMATIKA DAN KOMPUTER, 2018)
Behavior of sexual deviation is an unacceptable sexual behavior among the public. The lack of knowledge and the many obstacles to obtain information about early detection and community independence about sexual deviation and ignorance of the community in dealing with sexual deviation is also a factor not handled early. Forward chaining, consultation begins with a search of the premise or input data in the form of symptoms to the conclusion that is the conclusion of the type of deviation behavior as well as the solution. From the above problems will be built Web-based system that serves to detect the beginning independently of the perceived disorders that can be accessed with an extensive lap and time is not limited.The system is built using PHP and MySQL programming as the database. The method used for forwarding is forward chaining. While the results of the diagnosis will inform about the diagnosis of the list of symptoms included, information on the results of the rules of the disorder suffered and information about the possibility of handling can be done.Black box testing techniques are emphasized on data entry, output data, system functions, performance, and initialization in the system. While testing the alpha test is done by inviting 10 respondents testing is emphasized on the interface, dialogue, and information generated. From the results of testing the alpha test shows that the system created has been running well and produce information that is accurate, and easy to understand.